Variation in the ovine MYF5 gene and its effect on carcass lean meat yield in New Zealand Romney sheep. (September 2017) - Wang, Jiqing; Zhou, Huitong; Forrest, Rachel H.J.; Hu, Jiang; Liu, Xiu; Li, Shaobin; Luo, Yuzhu; Hickford, Jon G.H.
Abstract: Myogenic factor 5 (MYF5) plays an important role in regulating skeletal muscle, but to date there have been no reports on whether the gene is variable and whether this variation is associated with meat yield in sheep. In this study, four variants ( A to D ) of ovine MYF5 containing two Single Nucleotide Polymorphisms (SNPs) and one basepair (bp) insertion/deletion were detected by Polymerase Chain Reaction – Single Stranded Conformational Polymorphism (PCR-SSCP) analysis. Breed differences in variant frequencies were observed. The effect of variation in ovine MYF5 on lean meat yield, predicted using VIAScan® technology, was investigated in 388 male NZ Romney lambs. Only genotypes AA and AB were found in these lambs. Lambs with genotype AA had a higher leg yield ( P = 0.044), loin yield ( P = 0.002) and total yield ( P = 0.012) than those with genotype AB . No association with shoulder yield was detected. These results suggest that ovine MYF5 may be a valuable genetic marker for improved lean meat yield. Highlights: Four variants of ovine MYF5 are identified by PCR-SSCP. An insertion/deletion is found in intron 2 and two SNPs are found in exon 3 coding sequence. Variants differ in frequencies between breeds. Variation in MYF5 affects leg yield, loin yield and total yield in NZ Romney sheep.